PERENCANAAN PAKET WISATA TRACKING DESA TENGANAN KECAMATAN MANGGIS KABUPATEN KARANGASEM-BALI - Ni Nyoman Padmi Triyanti; I Ketut Suwena; I Putu Sudana (Jurnal IPTA, 2017)
Tenganan village of Karangasem regency is one of the ancient Balinese village. Tenganan village has the potential to be used as a variety of attractions both natural and cultural potential. One is the tourist tracking. Given that there are many potential Tenganan village that can be used as a tracking tour, but have not got a touch of communities and local governments. Lack of promotion and accessibility is one obstacle why several other attractions have not been able to flourish. In this regard, the issues raised are (1) what potential there is in Karangasem regency which is used as a tracking tour? (2) How to plan a tour package tracking can be developed to support the potential in Tenganan village?